Methodology of mathematical economics and econometrics - Tintner, Gerhard (Chicago: University of Chicago Press, 1968)
This essay attempts to present some methodological problems of mathematical economics and econometrics, and also of operations research (econometrics of enterprise), to a public which does not necessarily consists of economists.
"Also issued as Vol. II, no. 6, of the International encyclopedia of unified science."
Bibliography: p. 101-113.
rpm 07/08/2017
Loans
Keywords: Economics, Mathematical; Econometrics; Econometrics method